HMGA1 Induction of miR-103/107 Forms a Negative Feedback Loop to Regulate Autophagy in MPTP Model of Parkinson’s Disease - Li, Gehui; Luo, Wanxian; Wang, Baoyan; Qian, Chen; Ye, Yongyi; Li, Yuantao; Zhang, Shizhong (Frontiers in Cellular Neuroscience, 2021)
Autophagy dysfunction has been directly linked with the onset and progression of Parkinson's disease (PD), but the underlying mechanisms are not well understood. High-mobility group A1 (HMGA1), well-known chromatin remodeling proteins, play pivotal roles in diverse biological processes and diseases. Their function in neural cell death in PD, however, have not yet been fully elucidated. Here, we report that HMGA1 is highly induced during dopaminergic cell death in cell culture and murine models of PD. Functional studies using genetic knockdown of endogenous HMGA1 show that HMGA1 signaling inhibition accelerates neural cell death, at least partially through aggravating MPP+-induced autophagic flux reduction resulting from partial block in autophagic flux at the terminal stages, indicating a novel potential neuroprotective role for HMGA1 in dopaminergic neurons death. MicroRNA-103/107 (miR-103/107) family, which is highly expressed in neuron, coordinately ensures proper end-stage autophagy. We further illustrate that MPP+/MPTP-induced HMGA1 elevation counterparts the effect of miR-103/107 downregulation by directly binding to their promoters, respectively, sustaining their expression in MPP+-damaged MN9D cells and modulates autophagy through CDK5R1/CDK5 signaling pathway. We also find that HMGA1 is a direct target of miR-103/107 family. Thus, our results suggest that HMGA1 forms a negative feedback loop with miR-103/107-CDK5R1/CDK5 signaling to regulate the MPP+/MPTP-induced autophagy impairment and neural cell death. Collectively, we identify a paradigm for compensatory neuroprotective HMGA1 signaling in dopaminergic neurons that could have important therapeutic implications for PD.